PENGARUH KEMUDAHAN DAN PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK PENGHASILAN ORANG PRIBADI ( Studi di Kantor Pelayanan Pajak Pratama Bantul ) - Dwi Woro Setiyoningrum (Jurnal Akuntansi, 2014)
This study discusses the influence of convenience and service to the taxpayer compliance in paying income tax. This study was performed at the Tax Office Primary Bantul. The purpose of this research is to determine whether the facilities and services affect taxpayer compliance and what efforts Bantul Pratama Tax Office in improving tax compliance. This study is built with two hypotheses, namely: (1) ease in the rocessoftaxation, (2) positive effect Compliance Services The type of data in this study is primary data, with sampling at Bantul Pratama Tax Office using incidental sampling technique. Questionnaires were used as a sample of 100 and only return 90. This research is kualtitatif, and testing using multiple linear regression statistical tests. The results of this study indicate that two simultaneous independent variables significantly influence adherence. Partially shown that convenience has a positive and significant effect on adherence. While the service has a positive effect but not significant effect on compliance. Keywords : Taxpayer Compliance, Convenience in Paying tax, Service tax